Magnetic resonance imaging findings in ovarian torsion post in vitro fertilization - Al Salmi, Ishaq S. (Radiol Case Rep, 2018)
Patients who get pregnant after being treated with in vitro fertilization (IVF) are at significantly increased risk of ovarian torsion compared to the general population and also in comparison to patients who get pregnant normally [1,2]. The risk is further increased in patients who develop ovarian hyperstimulation syndrome [1]. This possibility should be considered in this group of patients presenting with acute abdominal pain and immediate management should be commenced. Here, we report 2 patients who received treatment for infertility with IVF and developed ovarian torsion and we discuss their management including the imaging workup. The first case is a 34-year-old woman at 11 + 3 weeks of gestation after IVF who presented with a 12-hour acute right lower abdominal pain with nausea and vomiting. She underwent an ultrasound examination and then further evaluated with magnetic resonance imaging which showed asymmetric enlargement of the right ovary and stromal edema and a diagnosis of ovarian torsion was made. The patient underwent laparoscopic detortion and the ovary was salvaged. The second case is a 33-year-old woman at 9 weeks of gestation after IVF who presented with intermittent abdominal pain, vaginal bleeding, and nausea and vomiting for 5 days but became worse on the fifth day. Ultrasound and subsequently magnetic resonance imaging were performed which confirmed hyperstimulation syndrome. Abnormal location of the left ovary anterior to the uterus with higher volume as well as the clinical progression raised the possibility of ovarian torsion and prompted a diagnostic laparoscopy which showed right ovarian torsion and detortion was performed.